Towards a sustainable university transition model for emerging markets - Quang Hung Bui; Tu Anh Trinh; Hanh An Le Thi; Nhu Quynh Phan; Hoang Uyen Nguyen Dinh (Cogent Business & Management, 2023)
The growing importance of a sustainable university transition model is evident in developing countries, where the challenge lies in balancing economic growth, social well-being, and environmental protection. This is further complicated by the need to address global issues locally, known as glocal perspectives, and reconcile short-term versus long-term thinking. Sustainable universities (SU) go beyond traditional roles by incorporating sustainability into daily operations. However, universities in emerging markets differ significantly from mature institutions in developed countries, facing limited autonomy and unique social and prioritization factors. Therefore, it is essential to consider the differences between universities in various stages when developing a sustainable university strategy. A narrative literature review methodology was utilized, involving literature search and screening, data extraction, and analysis to provide insights into several relevant models for approaching and implementing SU in emerging markets. The proposed model accentuates the "Sustainability on Campus" concept, a nexus between Education, Research, and Connecting communities with a shared interest in sustainability. It extends the university campus's role beyond a test bed and strives to inculcate sustainable practices within every facet of the institution, encompassing global, national, regional, organizational, and individual levels. Moreover, this approach seeks to contribute significantly to the national economy as part of the institution's third mission.
Keywords: 650; developing country; emerging market; sustainability; sustainable university; transition model